The Role of School in Preventing the Marginalization of Poor Students - Łobacz, Małgorzata (Multidisciplinary Journal of School Education, 2015)
Poverty, if it is not properly viewed by the public, may lead to the depersonalization of both poor and living in the midst of those who need help. Poverty is experienced by children in a specikc way. They often suher from hunger, they are undernourished, and they have limited access to a variety of goods, including culture and education. This, in turn, is often relected in their self-esteem, a sense of self-dignity. The role of the school in kghting the poverty of the students is shown in this article. The existing forms of aid to poor students are presented, as well as the challenges facing the school in terms of helping marginalized students. It is also crucial for the teachers themselves to be trained in such a way that would promote not only the intellectual development of the students, but most of all – the pro-social attitudes and that would emphasize the value and dignity of a person.